Penerapan Metode SAW Untuk Sistem Pendukung Keputusan Pemilihan Dosen Terbaik Program Studi S1 Sistem Dan Teknologi Informasi Institut Teknologi Dan Bisnis (ITB) Semarang - Permata Sari, Lavenia Permata Sari; Andreas Tigor Oktaga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
The purpose of this research is to reveal the advantages of the Simple Additive Weighting (SAW) method in measuring the performance of the lecturer to produce the best lecturer assessment The research uses the purposive sampling method in determining the student participants who have received learning from the sample of the research, namely five lecturers at the S1 System and Information Technology (STI) Study Program of the Institute of Technology and Business (ITB) Semarang in the course of TA. 2020/2021-2022/2023 to give the assessment based on the criteria used, Pedagogical, Professional, Personality, Social. The results of this study obtained the calculations of docent 1 (A1) with a total of 0.85, docent 2 (A2) with a Total of 0.8, docent 3 (A3) with a Total of 0. 8, docent 4 (A4) with a totall of 0.6, and docent 5 (A5) with a TOTAL of 1.00. So it can be concluded that the decision support system using the SAW method showed that with the highest score of docents 5 (A5).